3D nano/microfabrication techniques and nanobiomaterials for neural tissue regeneration. (May 2014) - Zhu, Wei; O'Brien, Christopher; O'Brien, Joseph R; Zhang, Lijie Grace
Injuries of the nervous system occur commonly among people of many different ages and backgrounds. Currently, there are no effective strategies to improve neural regeneration; however, tissue engineering provides a promising avenue for regeneration of many tissue types, including the neural context. Functional nerve conduits derived from tissue engineering techniques present bioengineered 3D artificial substitutes for implantation and rehabilitation of injured nerves. In particular, nanotechnology as a versatile vehicle to create biomimetic nanostructured tissue-engineered neural scaffolds provides great potential for the development of innovative and successful nerve grafts. Nanostructured conduits derived from traditional and novel tissue engineering techniques have been shown to be superior for successful neural function construction due to a high degree of biomimetic character. In this paper, we will focus on current progress in developing 3D nano/microstructured neural scaffolds via electrospinning, emerging 3D printing and self-assembly techniques, nanobiomaterials and bioactive cues for enhanced neural tissue regeneration.